Analyzing the Need for Ethnoscience-Integrated Digital Resources in Coastal Chemistry Education - Fitriah Khoirunnisa; Dina Fitriyah; Rita Fitriani; Bony Irawan; Muhamad Al Rasyid (Universitas Syiah Kuala, 2026)
Despite the growing emphasis on technology-enhanced and context-based learning in chemistry education, the availability of structured digital learning resources that integrate local wisdom remains limited, particularly in coastal contexts. This gap may hinder pre-service chemistry teachers from connecting scientific concepts with culturally relevant knowledge and local environmental issues. Therefore, this study aimed to analyze the need for designing an ethnoscience-integrated digital learning resource for coastal chemistry education. This study employed a needs analysis approach within a design and development research framework, involving 24 pre-service chemistry teachers at Raja Ali Haji Maritime University. Open-ended and closed-ended questionnaires were used to gather the data, which were then descriptively analyzed. The results showed a substantial lack of learning resources: 91.7% of participants had never come across pertinent materials at the library, and all participants (100%) reported not having a primary digital learning resource. The majority of students (95.8%) used disjointed sources, including unstructured online content and journal articles. Just 8.33% of students showed a thorough comprehension of ethnoscience, despite the fact that 75% of them were aware with it. These results show that an organized, technologically assisted, and contextually appropriate learning resource is desperately needed. This study adds to culturally sensitive and technologically advanced chemistry teaching, especially in coastal situations, and offers an empirical foundation for the creation of ethnoscience-integrated digital learning resources